Planning Analysis and Efficiency Comparison of On-Grid, Off-Grid, and Hybrid Grid-Tied Rooftop Solar Power Systems for the Development of the Control Building of Perum Jasa Tirta 1/3, WS Brantas Division - Nindia Nova Novena; Royb Fatkhur Rizal (Jurnal Engine: Energi, Manufaktur, dan Material, 2026)
Perum Jasa Tirta I, WS Brantas Division in the Tulungagung working area, experiences unreliable electricity supply due to frequent outages, requiring an alternative solution through a rooftop photovoltaic (PV) system. This study aims to design and evaluate the performance and techno-economic feasibility of three configurations: On-Grid, Off-Grid, and Hybrid Grid-Tied systems. Based on the energy consumption analysis, the total demand is 233.5 kWh/day or 85,192.10 kWh/year. By considering system losses of 25% and an Equivalent Sun Hours (ESH) value of 4.5 hours/day, the required PV capacity is 69.18 kW, using 93 modules of 750 Wp. Simulation results using Homer Pro show that the On-Grid system generates 166,208 kWh/year, the off-grid system produces 123,361 kWh/year, and the hybrid grid-tied system generates 140,699 kWh/year. All systems are capable of meeting the load demand, with different levels of energy surplus. From a techno-economic perspective, the off-grid system provides the highest return with an NPV of IDR 11.2 billion and an IRR of 128%, but it is relatively overdesigned and highly dependent on batteries. The on-grid system offers lower investment costs but depends on the utility grid. Meanwhile, the hybrid system shows balanced performance and is considered the optimal solution.